Case Report: A new variant of the forehead flap for subtotal nose reconstruction in a single stage: the dragonfly flap - Brambullo, Tito; Franchi, Arianna; Masciopinto, Giuseppe; De Lazzari, Alberto; Vindigni, Vincenzo; Bassetto, Franco (Frontiers in Surgery, 2024)
Background. The forehead flap is probably the most used method for nose reconstruction after cancer resection. During the past century, this technique has been continuously refined to achieve better functional and aesthetic outcomes. Different variations have been described, with the original technique being modified based on tissue loss, the layer to be replaced, and the management of the donor area. Methods. We propose a new and innovative version of the forehead flap in which both the forehead skin and the frontal muscle are harvested simultaneously using the same vascular pedicle. Partially separating the two layers allows muscle tissue to replace the inner layer and cover the nasal septum framework, while the skin will replace the outer layer. The nostrils are reconstructed simultaneously using bilateral hinge-over lining skin flaps harvested from the nasal folds. Results. Step by step, a schematic illustration of the technique is given, followed by a complete report on a successful total nose reconstruction case. Conclusions. Despite the increasing number of techniques which have been introduced to achieve full reconstruction of the nose, including microsurgical tissue transfer, the simultaneous replacement of both the inner and outer layers continues to be an issue for the plastic surgeon. In this article, we suggest a solution for total nose reconstruction in a single-stage procedure.